The production of seedlings via vegetative propagation and the construction of knowledge in the school context (Research, Society and Development, 2021)
The present work aimed to propose learning situations by means of the production of seedlings of Maytenus by minicutting, providing the articulation of theoretical-practical knowledge of Botany leading. The project was developed in the form of a Botany Workshop, with a 9th grade class. The data collection instruments were pre- and post-questionnaire, in addition to photos and observations, and the methodology of the research used was qualiquantitative. It was concluded that the students know and use medicinal plants, as well as their forms of propagation. The project contributed to the training of students, since 60% considered the activities excellent, 33% optimal and 7% good.